An Analysis of Auditors’ Characteristic and Non-Characteristic Components on Detecting The Fraudulent Occurrences in Public Sectors - Aisyaturrahmi (jfpublisher, 2022)
This study is to examine the influence of the auditors’ characteristic and non-characteristic components on detecting the fraudulent occurrences in the public sectors. Specifically, this study focuses on financial statement fraud as it has the most negative impacts on the society and beyond. This study is developed by the empirical evidence from Indonesian external auditors. The author in the initial stage creates hypotheses to explain the interaction processes between the auditors’ characteristic and non-characteristic components on detecting the fraudulent occurrences in the public sectors. The results of this study concluded that audit procedures and strategies have a significant effect on detecting financial statement fraud in public sector organizations. Meanwhile, The auditors competence is not significantly responsible in detecting financial statement fraud in public sector organizations. The auditors independence and professional skepticism has a significant effect on detecting fraudulent reports in public sector organizations. Thus, the auditor objectivity has no significant effect on the success of detecting financial statement fraud in public sector organizations.